Preparation method of fluorine-free super-hydrophobic surface
Patent Information
- Application Number
- CN202611343348.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的是要解决现有铝合金超疏水表面的加工方法存在成本高、工艺复杂、不环保和稳定性差的问题,而提供一种无氟超疏水表面的制备方法
[0015]一、本发明利用纳秒激光表面处理技术,旨在实现绿色便捷的超疏水表面加工工艺,实现铝合金超疏水表面的绿色环保加工,简化超疏水表面加工工艺,提供一个绿色便捷的表面加工新途径的新思路,解决传统超疏水表面加工方法存在成本高、工艺复杂、不环保等问题;
Smart Images

Figure CN122875932A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of surface engineering and biomimetic materials technology, specifically relating to a method for preparing a fluorine-free superhydrophobic surface. Background Technology
[0002] 3003 aluminum alloy, a typical Al-Mn series rust-resistant aluminum alloy, is widely used in key structural components such as automotive radiators, heater core fins, and battery trays and housings for new energy vehicles due to its low density, good processability, high specific strength, and excellent corrosion resistance and thermal conductivity. However, commercial aluminum alloy materials naturally exhibit hydrophilicity on their surface. When operating in humid, low-temperature condensation, or high-dust industrial environments, they are prone to water accumulation, frost formation, and ice buildup. This not only degrades heat exchange efficiency but also induces localized electrochemical corrosion and battery housing insulation failure, severely shortening the service life of critical components.
[0003] Modifying metal surfaces into superhydrophobic surfaces is an effective means to achieve self-cleaning, anti-icing, drag reduction, and long-term corrosion protection. Conventional superhydrophobic surface preparation methods (such as chemical acid-base etching, sol-gel methods, and electrochemical anodizing) often rely on fluorinated silane coupling agents or perfluoropolymers for wetting modification to reduce surface energy. Such fluoride chemical modifications have fatal flaws such as persistent environmental toxicity (PFAS hazard), easy decomposition and desorption at high temperatures, and weak adhesion to the substrate, making it difficult to meet the requirements of green manufacturing and harsh industrial environments.
[0004] Many plant leaves in nature exhibit excellent hydrophobic and antifouling properties. Previous studies have mostly focused on classic models such as lotus leaves; however, the microscopic structures of plants in nature are diverse. Research has found that while honeycomb structures themselves do not possess superhydrophobic properties, superhydrophobicity can be achieved by laser processing to mimic hexagonal honeycomb structures and then combining this with heat treatment to reduce their surface energy. Furthermore, the underside of the leaf of *Metaplexis japonica* is composed of micron-sized irregular papillae, localized stomatal depressions, and interwoven micro-folds, exhibiting a strong ability to trap air and reduce the solid-liquid contact area. Therefore, exploring the use of honeycomb and *Metaplexis japonica* leaves as biomimetic prototypes, combined with green controlled nanosecond laser processing and fluorine-free surface energy modulation technology, has significant practical value for developing novel industrial-grade superhydrophobic surfaces for aluminum alloys. Summary of the Invention
[0005] The purpose of this invention is to solve the problems of high cost, complex process, environmental unfriendliness and poor stability of existing aluminum alloy superhydrophobic surface processing methods, and to provide a method for preparing fluorine-free superhydrophobic surfaces.
[0006] This invention proposes a green processing technology based on nanosecond lasers, aiming to achieve an environmentally friendly and efficient surface treatment technology and realize the preparation of green and pollution-free superhydrophobic surfaces. This invention uses laser etching technology to precisely construct biomimetic micro-nano structures by controlling laser power, scanning speed and processing shape, simulating natural superhydrophobic surfaces and providing a new approach for utilization.
[0007] A method for preparing a fluorine-free superhydrophobic surface is specifically carried out according to the following steps:
[0008] 1. Perform ultrasonic cleaning on the aluminum alloy substrate to remove oil and organic impurities from its surface;
[0009] 2. Place the cleaned aluminum alloy substrate in a clean and ventilated environment to air dry naturally to obtain the pretreated aluminum alloy substrate.
[0010] 3. The pretreated aluminum alloy substrate is placed under a nanosecond laser and processed according to the set wavelength, pulse width, frequency, focal length, laser spot radius, laser power, scanning speed and processing pattern. The surface of the aluminum alloy substrate is precisely ablated by the nanosecond laser pulse to form periodic micron-level grooves and nano-level protrusions, thus obtaining an aluminum alloy substrate containing micro-nano structures.
[0011] Fourth, the aluminum alloy substrate containing micro-nano structures is placed in a vacuum constant temperature furnace for heat treatment to form a fluorine-free superhydrophobic surface on the surface of the aluminum alloy substrate.
[0012] The principle of this invention:
[0013] This invention relates to nanosecond laser surface treatment technology. It utilizes nanosecond laser pulses to precisely ablate aluminum alloy surfaces, forming periodic micron-scale trenches and nanoscale protrusions. Depending on the specific nano- and micro-structures, processing power, and processing speed, combined with surface heat treatment, the efficiency of these multi-scale rough structures in incorporating low surface energy materials (such as hydrocarbons adsorbed from the air) is improved, achieving superhydrophobic properties with a contact angle >150°. The process method of this invention employs direct surface processing combined with heat treatment, avoiding the use of chemical reagents and the generation of wastewater. Simultaneously, the controlled variables, such as scanning speed, frequency, and power, directly affect the surface morphology and hydrophobic properties, facilitating control. By controlling the laser distance from the metal surface at 31.9 cm, the metal surface is locally heated and melted under nanosecond laser processing. Laser ablation of the material achieves surface etching and morphology control. Processing in air eliminates the need for auxiliary gases, allowing natural oxidation to form a low surface energy layer. Post-processing: Low-temperature heat treatment promotes the adsorption of organic matter on the surface. This invention can process different micro- and nano-scale regular patterns on metal surfaces to obtain different nano- and micro-structures and hydrophobic properties.
[0014] Advantages of this invention:
[0015] I. This invention utilizes nanosecond laser surface treatment technology to achieve a green and convenient superhydrophobic surface processing technology, realize the green and environmentally friendly processing of superhydrophobic aluminum alloy surfaces, simplify the superhydrophobic surface processing technology, provide a new idea for a green and convenient surface processing approach, and solve the problems of high cost, complex process, and environmental non-environmental protection of traditional superhydrophobic surface processing methods.
[0016] Second, in this invention, the laser directly treats the metal surface without complex etching or low surface energy modification, avoiding the use of chemical reagents, making parameter control and process control simpler, facilitating digital control, making the processing process easy to adjust, and eliminating waste gas and waste liquid emissions, making it more environmentally friendly.
[0017] Third, this invention employs laser etching technology to precisely construct micro-nano structures by controlling laser power, scanning speed, and processing shape, simulating biomimetic honeycomb and natural superhydrophobic surfaces such as milkweed. This technology requires no complex chemical reagents, reduces pollution, and is easy to operate. In the experiment, after laser treatment, the surface contact angle of 3003 aluminum alloy increased significantly, exhibiting excellent superhydrophobic properties, providing a green and convenient new approach to surface processing for the field of materials science. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of a hexagonal honeycomb structure, where R is the inner circle radius and L is the side length.
[0019] Figure 2 The center points of the hexagonal honeycomb are arranged in a regular pattern to form an interlaced dot pattern;
[0020] Figure 3 This is a schematic diagram of a honeycomb structure using hexagons as the processing object;
[0021] Figure 4 This is a schematic diagram of a structure using a biomimetic circular array of milkweed as the processing object;
[0022] Figure 5 The images show a dot plot of the honeycomb center point as the processing object observed using a high-definition video microscope and a contact angle plot measured using a contact angle measuring instrument in Example 1.
[0023] Figure 6 The images show a honeycomb structure diagram with hexagons as the processing object observed using a high-definition video microscope in Example 2, and a contact angle diagram measured using a contact angle measuring instrument.
[0024] Figure 7 The images show the leaf surface of *Cynanchum paniculatum* (a type of milkweed) in Example 3, which was processed using a biomimetic circular array of *Cynanchum paniculatum*, as observed using a high-definition video microscope, and the contact angle measured using a contact angle measuring instrument. Detailed Implementation
[0025] Specific Implementation Method 1: This implementation method is a method for preparing a fluorine-free superhydrophobic surface, specifically completed according to the following steps:
[0026] 1. Perform ultrasonic cleaning on the aluminum alloy substrate to remove oil and organic impurities from its surface;
[0027] 2. Place the cleaned aluminum alloy substrate in a clean and ventilated environment to air dry naturally to obtain the pretreated aluminum alloy substrate.
[0028] 3. The pretreated aluminum alloy substrate is placed under a nanosecond laser and processed according to the set wavelength, pulse width, frequency, focal length, laser spot radius, laser power, scanning speed and processing pattern. The surface of the aluminum alloy substrate is precisely ablated by the nanosecond laser pulse to form periodic micron-level grooves and nano-level protrusions, thus obtaining an aluminum alloy substrate containing micro-nano structures.
[0029] Fourth, the aluminum alloy substrate containing micro-nano structures is placed in a vacuum constant temperature furnace for heat treatment to form a fluorine-free superhydrophobic surface on the surface of the aluminum alloy substrate.
[0030] Specific Implementation Method Two: This implementation method differs from Specific Implementation Method One in that: the aluminum alloy substrate mentioned in step one is aluminum alloy 3003, 3005, or 3105; the cleaning mentioned in step one involves ultrasonic cleaning with anhydrous ethanol and deionized water for 10-20 minutes respectively. Other steps are the same as in Specific Implementation Method One.
[0031] Specific Implementation Method Three: This implementation method differs from Specific Implementation Method One or Two in that the wavelength mentioned in step three is 1064nm. The other steps are the same as in Specific Implementation Method One or Two.
[0032] Specific Implementation Method Four: This implementation method differs from Specific Implementation Methods One to Three in that the pulse width in step three is 10 ns. The other steps are the same as in Specific Implementation Methods One to Three.
[0033] Specific Implementation Method Five: This implementation method differs from Specific Implementation Methods One to Four in that the frequency mentioned in step three is 20kHz to 80kHz. The other steps are the same as in Specific Implementation Methods One to Four.
[0034] Specific Implementation Method Six: The difference between this implementation method and Specific Implementation Methods One to Five is that the focal length mentioned in step three is 31.9cm to 32.9cm. The other steps are the same as in Specific Implementation Methods One to Five.
[0035] Specific Implementation Method Seven: The difference between this implementation method and Specific Implementation Methods One to Six is that the laser spot radius in step three is 0.01mm to 0.1mm. The other steps are the same as in Specific Implementation Methods One to Six.
[0036] Specific Implementation Method Eight: This implementation method differs from Specific Implementation Methods One to Seven in that: the laser power in step three is 12W~24W; the scanning speed in step three is 500~1000mm / s. Other steps are the same as in Specific Implementation Methods One to Seven.
[0037] Specific Implementation Method Nine: This implementation method differs from Specific Implementation Methods One to Eight in that the processing pattern described in step three is a honeycomb biomimetic hexagonal array, a dot pattern, or a milkweed biomimetic circular array. The other steps are the same as in Specific Implementation Methods One to Eight.
[0038] Specific Implementation Method Ten: The difference between this implementation method and Specific Implementation Methods One to Nine is that the heat treatment process described in step four is as follows: the temperature is increased from room temperature to 140°C to 160°C at a heating rate of 5°C / min to 10°C / min, maintained for 2 to 3 hours, and then cooled to room temperature in the furnace. The other steps are the same as those in Specific Implementation Methods One to Nine.
[0039] The beneficial effects of the present invention are verified using the following embodiments:
[0040] Example 1: A method for preparing a micro / nano-structured superhydrophobic surface, which uses the center point of a honeycomb structure as the processing target, and is specifically completed according to the following steps:
[0041] 1. Use anhydrous ethanol and deionized water to ultrasonically clean for 15 minutes each to remove oil and organic impurities from the surface of the aluminum alloy substrate.
[0042] The aluminum alloy substrate mentioned in step one is aluminum alloy 3003;
[0043] 2. Place the cleaned aluminum alloy substrate in a clean and ventilated environment to air dry naturally to obtain the pretreated aluminum alloy substrate.
[0044] 3. The pretreated aluminum alloy substrate is placed under a nanosecond laser and processed according to the set wavelength, pulse width, frequency, focal length, laser spot radius, power, scanning speed and processing pattern. The surface of the aluminum alloy substrate is precisely ablated by the nanosecond laser pulse to form periodic micron-level grooves and nano-level protrusions, thus obtaining an aluminum alloy substrate containing micro-nano structures.
[0045] The wavelength mentioned in step three is 1064nm, the pulse width is 10ns, the frequency is 30kHz, the focal length is 31.9cm, the laser spot radius is 0.05mm, the power is 60W, and the scanning speed is 60mm / s.
[0046] The processing pattern described in step three is a hexagonal array with a radius R of 0.04 mm and a side length L of 0.046 mm, with the center point of the honeycomb as the processing target;
[0047] IV. The aluminum alloy substrate containing micro-nano structures is placed in a vacuum constant temperature furnace for heat treatment to obtain a micro-nano structured superhydrophobic surface on the surface of the aluminum alloy substrate.
[0048] The heat treatment process described in step four is as follows: heating from room temperature to 150°C at a heating rate of 5°C / min, protecting for 2 hours, and then cooling to room temperature in the furnace.
[0049] Figure 5 The images show a dot plot of the honeycomb center point as the processing object observed using a high-definition video microscope and a contact angle plot measured using a contact angle measuring instrument in Example 1.
[0050] pass Figure 5 A high-definition video microscope revealed that its surface has an interlaced microporous structure. A micro-syringe dispensed 5-10 μL of water droplets, and the roll-off angle was measured to be 133.21° using a JY-82 contact angle meter.
[0051] Example 2: This example uses the center point of the honeycomb as the processing object. The difference from Example 1 is that the processing pattern in step three is a hexagonal array with a radius R of 0.07 mm and a side length L of 0.08 mm, using the center point of the honeycomb as the processing object; the power in step three is 24 W, and the scanning speed is 300 mm / s. Other steps and parameters are the same as in Example 1.
[0052] Figure 6 The images show a honeycomb structure diagram with hexagons as the processing object observed using a high-definition video microscope in Example 2, and a contact angle diagram measured using a contact angle measuring instrument.
[0053] pass Figure 6 A high-definition video microscope revealed that its surface has a hexagonal columnar structure; the roll-off angle measured by a JY-82 contact angle meter was 151.73°.
[0054] Example 3: This example uses a biomimetic milkweed circular array as the processing object. The difference from Example 1 is that the processing pattern in step three is a circular array, the programmed circular trajectory diameter is set to 63.0 μm, the edge-to-edge spacing between adjacent circular trajectories is 50 μm, the scanning speed is 779.1 mm / s, the laser power is 18.7 W, and the pulse frequency is 39.0 kHz. Other steps and parameters are the same as in Example 1.
[0055] Figure 7 The images show the leaf surface of *Calceolaria* (a type of milkweed) in Example 3, which was processed using a circular array, as observed using a high-definition video microscope, and the contact angle measured using a contact angle measuring instrument.
[0056] pass Figure 7A high-definition video microscope revealed that its surface has a spherical papillary structure, and the roll-off angle measured by the JY-82 contact angle measuring instrument was 155.06°.
Claims
1. A method for preparing a fluorine-free superhydrophobic surface, characterized in that... The preparation method is specifically carried out according to the following steps:
1. Perform ultrasonic cleaning on the aluminum alloy substrate to remove oil and organic impurities from its surface; 2. Place the cleaned aluminum alloy substrate in a clean and ventilated environment to air dry naturally to obtain the pretreated aluminum alloy substrate.
3. The pretreated aluminum alloy substrate is placed under a nanosecond laser and processed according to the set wavelength, pulse width, frequency, focal length, laser spot radius, laser power, scanning speed and processing pattern. The surface of the aluminum alloy substrate is precisely ablated by the nanosecond laser pulse to form periodic micron-level grooves and nano-level protrusions, thus obtaining an aluminum alloy substrate containing micro-nano structures. Fourth, the aluminum alloy substrate containing micro-nano structures is placed in a vacuum constant temperature furnace for heat treatment to form a fluorine-free superhydrophobic surface on the surface of the aluminum alloy substrate.
2. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The aluminum alloy substrate mentioned in step one is aluminum alloy 3003, 3005 or 3105; the cleaning mentioned in step one is to use anhydrous ethanol and deionized water to ultrasonically clean for 10 min to 20 min respectively.
3. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The wavelength mentioned in step three is 1064 nm.
4. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The pulse width mentioned in step three is 10 ns.
5. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The frequency mentioned in step three is 20kHz~80kHz.
6. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The focal length mentioned in step three is 31.9cm~32.9cm.
7. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The laser spot radius mentioned in step three is 0.01mm~0.1mm.
8. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The laser power mentioned in step three is 12W~24W; the scanning speed mentioned in step three is 500~1000mm / s.
9. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The processing pattern described in step three is a honeycomb biomimetic hexagonal array, a dot pattern, or a milkweed biomimetic circular array.
10. The method for preparing a fluorine-free superhydrophobic surface according to claim 1, characterized in that... The heat treatment process described in step four is as follows: heating from room temperature to 140℃~160℃ at a heating rate of 5℃ / min~10℃ / min, protecting for 2h~3h, and then cooling to room temperature in the furnace.